INDEKS KESESUAIAN WISATA PANTAI PULAU ZUM-ZUM MAC ARTHUR KABUPATEN KEPULAUAN MOROTAI - Aldy Adrianus Tatali (Jurnal Ilmu Pariwisata, 2024)
Zum Zum Mac Arthur Island is one of Morotai's flagship attractions promoted to tourists. This tourist island features accommodations or houses specifically designed for lodging, several gazebos for visitor relaxation, a statue of Mac Arthur (a colonial military commander), and a Zum Zum Mac Arthur Island name board standing on white sand. The Beach Tourism Suitability Index of Zum Zum Island is calculated at 92%. With a score exceeding 75%, the Zum Zum Beach area is highly suitable as a beach tourism destination. However, it would benefit from improved tourism facilities and infrastructure.